2021
DOI: 10.3389/fpls.2021.678202
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Myeloblastosis-Related Genes in Brassica napus L. and Positive Modulation of Osmotic Tolerance by BnMRD107

Abstract: Myeloblastosis (MYB)-related transcription factors comprise a large subfamily of the MYB family. They play significant roles in plant development and in stress responses. However, MYB-related proteins have not been comprehensively investigated in rapeseed (Brassica napus L.). In the present study, a genome-wide analysis of MYB-related transcription factors was performed in rapeseed. We identified 251 Brassica napus MYB (BnMYB)-related members, which were divided phylogenetically into five clades. Evolutionary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…For hormone treatment, five-week-old seedlings of B. napus line ‘J9712′, grown in a light incubator with 22 °C, 16 h light/8 h dark photocycle, were treated with 100 µM ABA, 100 µM kinetin (KT), 500 µM gibberellin (GA), 50 µM indoleacetic acid (IAA), and 10 µM strigolactone (SL). Three replicates of leaves were pooled respectively after 0 h, 1 h, 3 h, 6 h, and 12 h of treatment [ 74 , 75 ]. For osmotic, salt, and drought stresses, the ‘J9712′ seeds were germinated on 1/2 MS medium containing 150 mM mannitol, 150 mM NaCl, or 15% PEG.…”
Section: Methodsmentioning
confidence: 99%
“…For hormone treatment, five-week-old seedlings of B. napus line ‘J9712′, grown in a light incubator with 22 °C, 16 h light/8 h dark photocycle, were treated with 100 µM ABA, 100 µM kinetin (KT), 500 µM gibberellin (GA), 50 µM indoleacetic acid (IAA), and 10 µM strigolactone (SL). Three replicates of leaves were pooled respectively after 0 h, 1 h, 3 h, 6 h, and 12 h of treatment [ 74 , 75 ]. For osmotic, salt, and drought stresses, the ‘J9712′ seeds were germinated on 1/2 MS medium containing 150 mM mannitol, 150 mM NaCl, or 15% PEG.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Wan constructed a qRT-PCR assay to analyze the expression of GmMYB84 gene, and the results showed that both drought treatment and ABA treatment significantly increased the expression of the gene within 24 h [69]. The analysis of MYBrelated subfamily members in Brassica napus revealed a significant presence of BnMYBrelated genes containing cis-acting elements that displayed responsiveness to various hormones, including abscisic acid and gibberellin [70]. Twenty-one ethylene-responsive element binding-factor-associated amphiphilic repression (EAR) motifs were identified in the potato MYB family [71].…”
Section: Diversity Of Expression Profiles Of Myb Family Among Species...mentioning
confidence: 99%
“…In Morus alba, a total of 166 MYBs were identified [21]. A number of identifications and studies have also been published on MYB-related genes in other plants, including soybean [22], potato [23], Brassica napus L. [24], populus [9], pepper [25], and sweet osmanthus [26].…”
Section: Identification and Characterization Of The Myb Genesmentioning
confidence: 99%